Current status of conditioning regimens in haploidentical hematopoietic cell transplantation - Junichi Sugita; Masamitsu Yanada (Hematology)
The development of effective prophylaxis strategies against graft-versus-host disease (GVHD) has contributed to the widespread use of haploidentical related hematopoietic cell transplantation (Haplo-HCT). Currently, GVHD prophylaxis containing posttransplant cyclophosphamide (PTCY) is considered the standard of care in Haplo-HCT, and recent studies have shown comparable results for PTCY-based Haplo-HCT and HCT from other donor sources. The conditioning regimen plays an important role in eradicating tumor cells to prevent disease relapse and suppressing the recipient’s immune system to facilitate engraftment. PTCY-based Haplo-HCT was initially developed using a nonmyeloablative conditioning regimen consisting of fludarabine, cyclophosphamide and low-dose total body irradiation, but high relapse rates reinforced the need to intensify the conditioning regimen. In this respect, various myeloablative and reduced-intensity conditioning regimens have been investigated. However, the optimal conditioning regimens for PTCY-based Haplo-HCT have not yet been established, and this issue needs to be addressed based on data from patients undergoing the procedure. In this article, we review the existing literature on conditioning regimens for PTCY-based Haplo-HCT and discuss future perspectives.